Enhancing Students’ Critical Thinking Through an Ethnophysics Module with A Scaffolding Approach - Eveline, Erlin (Universitas Muhammadiyah Sumatera Utara (UMSU), 2025)
Contextual learning resources that follow the characteristics of students are still needed. Meanwhile, learning resources are still general and have not been adjusted to students’ characteristics and learning environments. In addition, the Indonesian curriculum aims to strengthen the profile of Pancasila students. Critical thinking is one of the six main characteristics of the Pancasila student profile. The ethnophysics module with a scaffolding approach can be a learning resource that provides information in the form of physics material combined with local wisdom to contextualise it with a scaffolding approach. The scaffolding approach is used for students to achieve their potential abilities, namely critical thinking. The study aimed to determine the effect of implementing the ethnophysics module with a scaffolding approach on students’ critical thinking skills. This study used an experimental method with a pretest-posttest control group design. The research subjects comprised 23 students from the experimental class and 29 from the control class. The test instrument consisted of pretest and post-test critical thinking questions. The study found a significant effect of the ethnophysics module with a scaffolding approach on students’ critical thinking skills, as seen from the n-gain score and effectiveness test using Mann-Whitney U on students' critical thinking skills as seen from the n-gain score and effectiveness test using Mann-Whitney U.Keyword : Critical thinking, ethnophysics, scaffolding approach